The monocyte to high-density lipoprotein cholesterol ratio is a risk factor for frequent premature ventricular complexes: a retrospective cohort study - Yunfei Wang; Deming Li; Xuetao Zhu; Jing Li; Cui Yue; Ling Wu; Qingqing Zhuan; Xiaomeng Dou; Wei Duan (Lipids in Health and Disease, 2022)
Abstract Background Little is known about the link between the monocyte to high-density lipoprotein cholesterol ratio (MHR) and frequent premature ventricular complexes (PVCs). This investigation aimed to evaluate the link between the MHR and frequent PVCs in patients, as well as their outcomes, using the axis, burden, coupling interval–ventricular tachycardia (ABC-VT) risk score (ARS). Methods Two hundred patients with frequent PVCs and 70 controls were retrospectively enrolled, and their general data were gathered. The MHR and ARS were calculated. Then, patients developing frequent PVCs were classified into a medium−/high-risk subgroup and a low-risk subgroup according to ARS. The results were evaluated employing comparative statistical analyses, Spearman’s correlation, logistic regression analyses, and receiver operating characteristic (ROC) curves. Results The MHR in the controls was obviously lower than that in the frequent PVC group. In addition, the MHR was the lowest in the control group and highest in the medium−/high-risk subgroup, with that of the low-risk subgroup falling in the middle. Spearman’s correlation analyses showed that the MHR was positively correlated with the ARS (ρ = 0.307, P < 0.001). Ultimately, the MHR was found to be a risk factor for frequent PVCs in the multivariate analysis. In addition, an MHR cutoff point of 254.6 featured 67.50% sensitivity and 67.14% specificity for predicting frequent PVCs, and the area under the curve (AUC) reached 0.694 (95% confidence interval: 0.623–0.766) (P < 0.001). Conclusions The MHR is positively and independently correlated with frequent PVCs and can be used as a practical, cost-saving and simple biomarker of inflammation owing to its value in predicting frequent PVCs. In addition, the MHR is crucial to risk stratification and prognosis, which may give it clinical value in the prevention and management of frequent PVCs.